Risk factors for readmission after ureteroscopy for stone disease: Modern single centre experience - Shuhei Hirano; Margaret A. Knoedler; Shuang Li; Emily C. Serrell; Ali S. Antar; Stephen Y. Nakada (BJUI Compass)
Abstract Objectives To identify factors that increase a patient's risk of readmission in the immediate postoperative period following ureteroscopy. Materials and Methods An IRB‐approved surgical database of patients with renal and ureteral stones at a single institution was retrospectively analysed for patients who underwent ureteroscopies and had 30 days follow‐up from September 2016 to June 2019. We reviewed the most recent 600 cases (300 consecutive women and 300 consecutive men). Patient characteristics including gender, body mass index (BMI) and comorbidities (hypertension, gout, diabetes mellitus (DM), recurrent urinary tract infections (UTIs), chronic kidney disease (CKD), bowel disease), history of preoperative ED visit and surgical factors (preoperative stent, stone size) were used to conduct univariate and multivariable logistic regression analysis. Outcome measures included readmission within 30 days postoperatively. Exclusion criteria included age <18 and <30 days follow‐up. Results Of the 600 patients, 40 (6.7%) visited the ED and 16 (2.7%) were admitted within 30 days postoperatively. None of the patient characteristics or surgical factors we examined were associated with ED visits postoperatively (all p > 0.05). Patients were more likely to have a postoperative admission if they were older (age 68 ± 15 vs 56 ± 15, p < 0.002; OR 1.06; 95% CI 1.01–1.10, p = 0.01) or had a history of recurrent UTIs (OR 7.40, 95%CI 1.78–30.67, p = 0.006). No other factors correlated with postoperative admissions. Conclusions Older age and history of recurrent UTIs increased patients' risks of readmission within 30 days of ureteroscopy. This finding is particularly important when hospital beds are at a premium. Older patients and patients with recurrent UTIs should be targeted for preoperative interventions to prevent readmission.